The effect and biological mechanism of COD/TN ratio on nitrogen removal in a novel upflow microaerobic sludge reactor treating manure-free piggery wastewater. (June 2016) - Li, Jianzheng; Meng, Jia; Li, Jiuling; Wang, Cheng; Deng, Kaiwen; Sun, Kai; Buelna, Gerardo
Highlights: An upflow microaerobic sludge reactor treating low COD/TN ratio piggery wastewater. Effect and biological mechanism of influent COD/TN ratio being investigated. Nitrifiers, hetero- and auto- trophic denitrifiers all thrived in the reactor. The nitrifiers and denitrifiers restricted by the increased influent COD/TN ratio. An influent COD/TN ratio less than 0.70 ensured a TN removal over 80% in the reactor. Abstract: A novel upflow microaerobic sludge reactor (UMSR) was constructed to treat manure-free piggery wastewater with high NH4 + -N concentration and low COD/TN ratio, and the effect and biological mechanism of COD/TN ratio on nitrogen removal were investigated at a constant hydraulic retention time of 8 h and 35 °C. The results showed that the UMSR could treat the wastewater with a better synchronous removal of COD, NH4 + -N and TN. The microaerobic UMSR allowed nitrifiers, and heterotrophic and autotrophic denitrifiers to thrive in the flocs, revealing a multiple nitrogen removal mechanism in the reactor. Both the nitrifiers and denitrifiers would be restricted by an influent COD/TN ratio more than 0.82, resulting in a decrease of TN removal in the UMSR. To get a TN removal over 80% with a TN load removal above 0.86 kg/(m 3 ·d) in the UMSR, the influent COD/TN ratio should be less than 0.70.